Tourist Perceptions of the Bambar Natural Pool Tourist Attraction in Waibu District, Jayapura Regency - Transna Putra Urip; Lambek Wonda; Vanessa D.P Pangke (AIBPM Publisher, 2024)
Local economic development is closely tied to the potential resources available within a region. In Jayapura Regency, the natural tourism sector plays a strategic role in promoting regional growth and improving community welfare. One such potential is the Bambar Natural Pool, a nature-based tourist attraction that requires continuous development to enhance visitor experiences. Understanding tourists’ perceptions is crucial in increasing the site’s competitiveness and attractiveness. This study aims to assess tourists’ perceptions of the Bambar Natural Pool based on three key variables: the condition of the tourist site, accessibility, and supporting facilities. Data were collected using a structured questionnaire and analyzed using descriptive quantitative methods. The findings reveal that tourists' overall perception of the Bambar Natural Pool is categorized as poor. Specifically, the site condition is rated as good (77.00%), while accessibility (66.67%) and facilities (61.40%) are rated as poor. These results highlight the need for creative development efforts that align with tourist expectations. Enhancing infrastructure and visitor support services is essential to elevate the appeal and competitiveness of this natural attraction. Aligning development strategies with tourists' perceptions can help ensure that improvements meet visitor needs and encourage more sustainable tourism growth in the region.